Auké - A Ilha Invisível: pintura e dramaturgia - Albuquerque, Ricardo Bezerra de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
O trabalho apresenta o processo de criação do texto dramatúrgico Auké - A Ilha Invisível e a produção pictórica criada especificamente para ele. O texto dramatúrgico discute os desdobramentos que a comunicação cria a partir do encontro entre personagens oriundos de mundos diferentes e os desentendimentos relacionais consequentes. O trabalho busca integrar a pintura com a dramaturgia teatral para compor uma nova sintaxe estética tanto visual quanto teatral a partir das afinidades e diferenças entre as duas linguagens. A tese aborda também a transformação da pintura ao estar nesse novo lugar que não é o espaço expositivo tradicional público e/ou privado. A pesquisa revela o processo de escrita do texto dramatúrgico e o resultado obtido dessa inter-relação com a pintura. Assim, a dramaturgia e a pintura ao se fundirem num propósito comum criam um campo conceitual e experimental que se desdobra em uma nova práxis artística.

The work presents the process of creation of the dramaturgic text Auké – A Ilha Invisível ( Auké – The Invisible Island) and the pictorial production specially created for it. The dramaturgic text discusses the unfolding ways that communication creates from the meeting of the characters coming from different worlds and the consequent quarrels in their relationship; The work aims at integrating the painting with theatrical dramaturgy to compose a new aesthetics syntax both visual as well as theatrical starting with the similarities and differences between the two languages. The thesis also approaches the transformation of picture by being in that new place which is not the private and or public traditional space for exhibition. The research reveals the process of writing the dramaturgic text and the result obtained out of that interrelation with the painting. Therefore, the dramaturgy and the painting when merging in a common purpose create a conceptual and experimental field that unfolds into a new artistic practice.
Auké - The Invisible Island: painting and dramaturgy
Keywords: Arte contemporânea; Pintura; Teatro; Linguagem visual; Linguagem teatral; Site specific